INFLUENCE OF CADRE TRAINING IN INCREASING TOOTHBRUSHING ACTION IN PREGNANT WOMEN - Francisca Fatima De Sena; Bedjo Santoso; Diyah Fatmasari; Lanny Sunarjo; Waljuni Astu Rahman (Journal of Applied Health Management and Technology, 2020)
ABSTRACTProblems on dental and oral hygiene are caused by poor dental and oral care. A viable strategy in changing the behavior of pregnant women is through dental hygiene counseling. We present solution for counseling with material which could be heeded by pregnant women. The aim of the research is to improve knowledge, attitude and action to take care of dental and oral hygiene, so that the target can do self-care to dental and oral hygiene. We implemented Research and Development (RD) method comprising 5 stages, namely, information collection, design and build, expert validation and revision, model test and final model results. This was done with the subject in as much as 50 pregnant women. The sample used a purposive sampling technique. Data were tested using intraclass correlation coefficient and paired sample test. The results show that Primary Health Center cadre training is effective in improving the dental and oral hygiene action in pregnant women.